The Effectiveness of the Ethnophysics-Based PBL Model in Enhancing Scientific Literacy on Newton's Laws - Listian Nur Hafidloh; Eko Hariyono; Maharani Agustina Arivi (National Dong Hwa University, 2025)
This study aims to examine the effectiveness of a Problem-Based Learning (PBL) model integrated with ethnophysics in enhancing students' scientific literacy on Newton’s Laws. The low level of scientific literacy among students underscores the need for a contextualized learning approach through the integration of local wisdom, specifically, the use of Becak Lawu as an instructional context. A quasi-experimental method with a nonequivalent control group design involved two eleventh-grade classes selected through purposive sampling. Class XI-2 as the experimental class with 35 students and class XI-5 as the control class with 36 students The research instruments consisted of a questionnaire on students' responses to the science literacy of Newton's Laws material. Data were analyzed using SPSS. The results indicate that the lesson implementation reached ≥88%, categorized as very good. The experimental group achieved an N-Gain of 0.53 (moderate), while the control group obtained 0.24 (low). Item number 1 is in the moderate category, and item number 3 is in the difficult category, and student responses to the learning model reached ≥86%, also categorized as very good. These findings suggest that the ethnophysics-based PBL model is effective in improving students’ scientific literacy.